PENINGKATAN KEMANDIRIAN SANTRI BERBASIS NILAI RELIGIUS DI PESANTREN - Fildza Avisyah; Junaidi, Junaidi (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2020)
The rapid development of the times, has implications for the implementation of education both non-formal education, formal education, and informal education is very necessary. Religious education is now known formally, not only in Islamic classes in the classroom by conveying material but Islamic religious lessons are also given in activities in Islamic boarding schools. Islamic boarding school is a unique system. Not only unique in the level of learning, but also in the values of life, the way of life adopted, the structure of the division of authority, and all other aspects of personality and society. This paper tries to explain explicitly about (1) Internalization of religious cultural values in increasing the independence of students of Salafiyah Syafi’iyah Sukorejo Islamic Boarding School. (2) The efforts of pesantren in enhancing religious cultural values at the Salafiyah Syafi’iyah Sukorejo Islamic Boarding School. In order to obtain new knowledge about the internalization of religious cultural values in increasing independence and the efforts of pesantren in improving religious culture.